Relevance of instrumented gait analysis in the prediction of the rebound phenomenon after guided growth intervention - Stief, Felix; Holder, Jana; Braun, Sebastian; Brenneis, Marco; van Drongelen, Stefan; Byrnes, S. Kimberly; Layher, Frank; Dussa, Chakravarthy U.; Meurer, Andrea; Böhm, Harald (Scientific Reports, 2024)
Predictors of rebound after correction of coronal plane deformities using temporary hemiepiphysiodesis (TH) are not well defined. The following research questions were tested: (1) Is the dynamic knee joint load useful to improve rebound prediction accuracy? (2) Does a large initial deformity play a critical role in rebound development? (3) Are BMI and a young age risk factors for rebound? Fifty children and adolescents with idiopathic knee valgus malalignment were included. A deviation of the mechanical femorotibial angle (MFA) of ≥ 3° into valgus between explantation and the one-year follow-up period was chosen to classify a rebound. A rebound was detected in 22 of the 50 patients (44%). Two predictors of rebound were identified: 1. reduced peak lateral knee joint contact force in the first half of the stance phase at the time of explantation (72.7% prediction); 2. minor initial deformity according to the MFA (70.5% prediction). The best prediction (75%) was obtained by including both parameters in the binary logistic regression method. A TH should not be advised in patients with a minor initial deformity of the leg axis. Dynamic knee joint loading using gait analysis and musculoskeletal modeling can be used to determine the optimum time to remove the plates.
CRIS-Team Scopus Importer:2024-10-11
Keywords: Dynamic knee joint loading; Gait analysis; Genu valgum; Leg malalignment; Rebound; Temporary hemiepiphysiodesis